Imperfect compromise : a new consensus among Israelis and Palestinians - Karpin, Michael I. (Washington, D.C. : Potomac Books, 2013)
The Middle East is now in the eye of a storm. But as this storm abates, an opportunity for peace and progress has emerged. In Imperfect Compromise, Michael Karpin, an Israeli broadcast journalist, presents a new thesis about the Middle East peace settlement. He lays out an optimistic forecast: The violent conflict between Arabs and Jews that has had the greatest negative impact on world peace since the end of the Cold War is moving steadily toward resolution. Moreover, since the first Zionists settled on the shore of the Lake of Galilee a hundred years ago, the relations between Arabs and Jew.
13 Softening the Hardest14 A Palestinian Easy to Like; 15 The Right of Return; PART IV BEYOND PROVINCIALITY: FACING EXTERNAL FACTORS; 16 Delayed Ignition; 17 A State of Isolation; 18 Iran-Two Scenarios, One Realistic; 19 The Bomb Is Still in the Basement; 20 Post-Assad; 21 The Next Cycle; 22 Critical Mass; 23 Apology and Compensation; Notes; Bibliography; Index; About the Author.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Arab-Israeli conflict -- 1993- -- Peace; Palestinian Arabs -- Politics and government -- 1993-; Zionism; Israel -- Politics and government -- 1993-; Palestine question (1948-); Conflit israélo-arabe -- 1993- -- Paix; Palestiniens -- Politique et gouvernement -- 1993-; Israël -- Politique et gouvernement -- 1993-; HISTORY -- Middle East -- Israel; Arab-Israeli conflict -- Peace; Palestinian Arabs -- Politics and government; Politics and government; Zionism; Israel; Nahostkonflikt; Friede; Since 1993